CAPITALIZATION OF BODY IN MODERN MUSIC VIDEOS - A. M. Pivovarov; D. V. Tkachuk (Дискурс, 2019)
The current article studies capitalization of body in the context of the sociological theory of Pierre Bourdieu and his followers. The results of the qualitative visual analysis of Russian music pop videos from the perspective of various patterns of using body as a physical, erotic and symbolic capital are demonstrated. Based on the data obtained, three main patterns of capitalization of corporeality are identified: body transformation that marks one's position in the social hierarchy, regulation of body images symbolic value, and legitimization of gender strategies used for erotic capital accumulation and conversion.